2015
DOI: 10.1083/jcb.2113oia259
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional repressor ZEB2 promotes terminal differentiation of CD8+ effector and memory T cell populations during infection

Abstract: In response to intracellular pathogens, CD8 + T cells are activated to proliferate and differentiate into a heterogeneous population of effector T cells, which are armed to eliminate infected cells. After pathogen clearance, the majority of effector CD8 + T cells die; however, a subset survives and differentiates to long-lived memory T cells. Should reinfection occur, these memory cells undergo rapid expansion and redifferentiation into effector cells, providing superior protection compared with naive T cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
48
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 28 publications
4
48
1
Order By: Relevance
“…In this study, we found that high amounts of T-bet induced Zeb2 mRNA expression and that ZEB2 was critical for the transcriptional programming of TE cell differentiation. To our knowledge, this study, along with that of Omilusik et al (2015), is the first to describe the function of ZEB2 in T cells. Overall, these data suggest that ZEB2 and T-bet enforce terminal effector differentiation through their cooperation by simultaneously inducing TE and repressing MP cell gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that high amounts of T-bet induced Zeb2 mRNA expression and that ZEB2 was critical for the transcriptional programming of TE cell differentiation. To our knowledge, this study, along with that of Omilusik et al (2015), is the first to describe the function of ZEB2 in T cells. Overall, these data suggest that ZEB2 and T-bet enforce terminal effector differentiation through their cooperation by simultaneously inducing TE and repressing MP cell gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…At least in the mouse, Bcell-intrinsic T-bet expression is also necessary for the production of IgG2A and effective antiviral humoral immunity. 99,100 DN2cells also express high amounts of ZEB2, a TF that acts cooperatively with T-bet to promote effector differentiation and inhibit memory differentiation in cytotoxic T cells 101,102. Importantly, despite sharing IL-21 receptor expression with naive cells, only naive cells express high levels of several repressors of effector differentiation including BACH2 which can directly repress PRDM1/BLIMP1,103 and FOXO1 which inhibits T-bet-mediated effector function in CD8 T cells 104.…”
mentioning
confidence: 99%
“…Importantly, despite sharing IL-21 receptor expression with naive cells, only naive cells express high levels of several repressors of effector differentiation including BACH2 which can directly repress PRDM1/BLIMP1,103 and FOXO1 which inhibits T-bet-mediated effector function in CD8 T cells 104. In distinction to DN2 cells, SWM and DN1 express high levels of TCF7 a TF that is repressed by T-bet/Zeb2, promotes central memory differentiation, and inhibits effector differentiation 102. In addition to the T-Bet/ Zeb2-regulated network, DN2 cells are characterized by high levels of expression of IRF4 and IRF4-regulated genes, in particular, of IRF4 target genes enriched in plasma cells.…”
mentioning
confidence: 99%
“…In oligodendrocyte precursors, where Zeb2 expression is low in abundance, activated Smads bind the coactivator histone acetyltransferase p300 and activate the expression of negative regulatory genes such as Id2 and Hes1; by contrast, in differentiating oligodendrocytes, expression of Olig1 and Olig2 induces Zeb2, which binds Smad-p300 complexes and represses expression of Id2 and Hes1 (24). Within the hematopoietic system, Zeb2 cooperates with Tbx21 (T-bet) to promote terminal maturation of natural killer (NK) cells and CD8 + T cells (25)(26)(27), and its inactivation results in broadly dysregulated hematopoiesis with prominent neutrophilia and loss of B cells and monocytes (28).…”
mentioning
confidence: 99%